Forging Identities in the Prehistory of Old Europe : Dividuals, Individuals and Communities, 7000-3000 BC - Chapman, John (Sidestone Press, 2020)
Of Chapters 6 and 7: the mortuary and domestic domains -- Chapter 8 -- Long-term settlement dynamics -- Introduction -- Settlement patterns by modern state -- Bulgaria -- The lands of 'former Yugoslavia' (Serbia, Republic of North Macedonia, Croatia, Slovenia, Kosova and Bosnia - Hercegovina) -- Settlement in Hungary -- Settlement in Romania, Moldova and Ukraine -- Chapter summary -- Chapter 9 -- Networks -- Introduction: an exotic pumice-stone -- Settlement networks -- Phase 1 networks -- Phase 2 networks -- Phase 3 networks -- Phase 4 networks -- Phase 5 networks -- Chapter summary.